COMBINATION OF CULTURE IN WEDDING RECEPTION BETWEEN BATAK ANGKOLA WITH JAVA YOGYAKARTA (Study case of a couple in Yogyakarta) - , RIKA ARSI FAZRINA TANJUNG, Supriyono, S.S., M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The graduating paper aims to learn about culture of wedding ceremony Batak Angkola and Java Yogyakarta. Then this final project describes about combination by intercultural couples differed in their wedding ceremony. Furthermore, the final project is expected to contribute to the educational institutions in providing additional information about the culture wedding ceremony of the people of Batak Angkola with Java Yogyakarta. Method of data collection is done in a way, interviews with couples who have two different cultures and also the study of librarianship. Interview the pair done at home between March and June. Study of librarianship to information gathering supporters in this final task. Based on interviews in a wedding culture among Batak Angkola with Java Yogyakarta there are several typical culture based combined in the marriage ceremony to honor the culture of each spouse.